Influencer relations: the new paradigm of public relations - Adi Sumandiyar; Juan Carlos M. Smith; Zulfia Hanum Alfi Syahr; Muhammad Najib Husain; Agung Suharyanto (Faculty of Communications Science, Dr. Soetomo University, 2023)
Digitalisation has become an integral part of people's daily lives, particularly with the significant impact of the COVID-19 pandemic. In the past, Public Relations (PR) primarily focused on public branding, catering mostly to a select audience. However, the rise of Digital Uses and Gratifications has led to a transformation in media dynamics, giving rise to a new paradigm known as Corporate Communications and Influencer Marketing. In this research, AI Machine learning and Pattern Analysis was employed to examine the patterns of the Influencer aspect within Public Relations. This emerging PR paradigm demonstrates the dynamic nature of the field as it expands to encompass new dimensions. Incorporating Influencer Relations to promote products requires integrating Corporate Communications skills to establish a thriving Influencer Relations industry. This highlights the evolving nature of PR in response to the changing media landscape, indicating the need for a comprehensive approach to harnessing the potential of digitalisation and Influencer Marketing in modern Public Relations practices.